A pragmática dos emojis na comunicação digital - Fernanda Teixeira Avelar (2018)
Taking into account the idea that Digital Communication (DC) presents hybrid characteristics, from written and oral modalities, the research analyzes the emojis, picture characters that may represent feelings, ideas, entities, states or events (EVANS 2015). The theoretical background of the study relies on the Theory of Politeness (BROWN AND LEVINSON 1978/1987) and the Theory of Face Work (GOFFMAN 2011). The research aimed at investigating the pragmatic- discursive potential of emojis, which is beyond mere expressions of emotions. It also aimed at verifying how the emojis contribute to the speakers (or users) communication of his intentions by means of what is typed. In order to do so, the following questions were listed: How emojis contribute to mitigate or intensify the illocucionary force of the speech acts they connect to? More specifically, how do they contribute to the face saving of the interactor who makes use of it? Data was collected through excerpts of interactions taken from a Whatsapp group with the consent of its members. The results corroborate the fact that not only do emojis work as elements attached to emotions, but they are also capable of expressing some intention of the speaker (or user) (DRESNER; HERRING 2010), in other words, they go beyond the mere communicatiion of emotive states in DC.